Coal Fly Ash as Adsorbent in Removing Organic Compounds (COD) From Tanah Tinggi Wastewater Treatment Installation in Tangerang City - Muhammad Djarkasih; Ratri Ariatmi Nugrahani; Nurul Hidayati Fithriyah (Journal of Applied Sciences and Advanced Technology, 2022)
Coal is a combustible organic mineral; the ash produced from burning coal is fly ash and bottom ash. This study aims to determine the process of treating fly ash waste from coal combustion by activating and characterizing it as an adsorbent and to obtain the best type of adsorbent with a concentration of coal fly ash as an adsorbent in removing organic compounds COD so that it meets the standards. Quality by accordance with the Regulation of the Minister of Environment and Forestry Number 68 of 2016 concerning Domestic Wastewater Quality Standards. The research will be carried out with 2 (two) processes, namely the process of making adsorbents and testing the application of fly ash adsorbents with variations in the concentration of sulfuric acid (H2SO4) 2.5%, 5%, and 10% and variations in stirring time of 60, 90, 120 and 150 minutes, then analyzed the COD (Chemical Oxygen Demand) content so that it meets the quality standards that have been set. The results showed that the fly ash content of coal has the potential to be used as an adsorbent because of the high SiO2 content of 35.8% and the Al2O3 content of 17.0%. Results The initial concentration of COD was 404 mg/l. The final concentration of COD for various stirring times with various H2SO4 activation was 11 mg/l with a stirring time of 150 minutes. Optimum conditions of removal efficiency (%) COD for variation of stirring time with various H2SO4 activation obtained 35.73%, R2 value = 0.9891, and the linear regression equation is y = 0.206x - 4.864 with the value of y is COD efficiency removal (%) and x is stirring time (minutes).